Dictionary of social and market research - Koschnick, Wolfgang J., 1942- (Hampshire, England ; Brookfield, VT : Gower, 1996)
Anyone working in the worlds of social or market research is faced with a daunting plethora of special terms, techniques and jargon covering everything from statistical methods through to specialized advertising and social science terminology. The Dictionary of Social and Market Research has been compiled to provide academics, researchers and professionals with an exhaustive reference work containing definitions for, and explanations of, terms, techniques and concepts from all areas of social and market research. Entries have been selected on the basis of their value in answering questions arising from both the theory and practice of social and market research. The 2,500 entries in Dictionary of Social and Market Research therefore provide an invaluable reference to the terminology that is increasingly encountered in these complex and specialized fields.
Keywords: Marketing research -- Dictionaries; Social sciences -- Research -- Dictionaries